2015
DOI: 10.1002/cam4.547
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of soft‐tissue sarcomas in Ireland

Abstract: Soft‐tissue sarcomas (STS) account for 1% of adult and 7% of pediatric malignancies. Histopathology and classification of these rare tumors requires further refinements. The aim of this paper is to describe the current incidence and survival of STS from 1994 to 2012 in Ireland and compare these with comparably coded international published reports. This is a retrospective, population study based on the data from the National Cancer Registry of Ireland (NCRI). Incidence and relative survival rates for STS in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
3
9
1
Order By: Relevance
“…The overall 5-year survival rate of the STS patient cohort after diagnosis was 56.4%, which was similar to that reported by other countries: Ireland (56%, 1994-2011) [20] and the United Kingdom (55%, 2006-2010) [21]; close to the European average (57.8%, 2000-2002) [6] but lower than in the United States (65%, 2006-2012) [25] and Japan (77.5%, 2006-2012) [15]. It should be noted that the Japanese study reported disease-specific survival rates.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The overall 5-year survival rate of the STS patient cohort after diagnosis was 56.4%, which was similar to that reported by other countries: Ireland (56%, 1994-2011) [20] and the United Kingdom (55%, 2006-2010) [21]; close to the European average (57.8%, 2000-2002) [6] but lower than in the United States (65%, 2006-2012) [25] and Japan (77.5%, 2006-2012) [15]. It should be noted that the Japanese study reported disease-specific survival rates.…”
Section: Discussionsupporting
confidence: 85%
“…The total incidence of STS in our analyses of Korea (2.49 per 100,000 person-years) is within the reported incidences. The incidence is lower when compared with the incidence rates of some countries or regions, for example the United States (4.2 per 100,000 person-years) [19], Europe (4.7 per 100,000 person-years) [6], Ireland (4.48 per 100,000 person-years) [20] and the United Kingdom (4.51 per 100,000 person-years) [21]. However, the incidence is higher than the incidence rate reported for Sweden (1.8 per 100,000 person-years) [22] and Beijing (1.15 per 100,000 person-years) [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the peak age of STS in Beijing was 80-84 years old [6], which may be related to the grouping method. The peak age of patients with STS initiated in extremities in Korea from 2009 to 2011 was 70-89 years old [12], and the peak age of STS patients in Ireland from 1994 to 2012 was 70-84 years old [13], which were different from the results in our study. The reason may be that the patients of STS only in extremities were analyzed in Korea, but not in the whole body excluding visceral sarcoma; and the research in Ireland was about the STS in whole body including visceral sarcoma.…”
Section: Discussioncontrasting
confidence: 99%
“…The lower peak age in the study may be related to it including embryonal rhabdomyosarcoma with the lower age of onset. The peak age of STS of the extremities in Korea from 2009 to 2011 was 70-89 years old [13], and the peak age of STS in Ireland from 1994 to 2012 was 70-84 years old [14], which were different from the results of the study. The reason may be that the result in Korea mainly studies STS of the extremities, but not the whole body (excluding visceral sarcoma), and the research in Ireland was about the whole body including visceral sarcoma.…”
Section: Discussionmentioning
confidence: 59%